Rediscovering Mary Parker Follett: Rare Gem in Public Administration Scholarship in the Early 20th Century - Abad-Sarmiento, La Rainne (Philippine Journal of Public Administration; Vol 55 No 1&2 (2011), 2017)
Mary Parker Follett was a pioneering public administration theorist and one of the few women who braved the male dominated fields of management and organization studies in the United States in the early part of the 1900s. Even though she wrote about management and organization environment and processes a century ago, the concepts and themes she envisioned then such as power and authority, conflict resolution, democratic principles in the organization, and governance now resonate in contemporary fundamentals. Her prolific efforts to define the ideal humane and democratic organization and effective governance make this modernist and valiant social worker, advocate, management scholar and consultant rightly be described as “prophet of management.”
Keywords: Mary Parker Follett, Public Administration theory, management studies, organization studies